The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ma14227006
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Angulated Screw-Channels in Metal-Free, Implant-Supported Restorations: A Retrospective Survival Analysis

Abstract: Angulated screw channels (ASC) allow the clinician to reposition the access hole of screw-retained restorations, improving the design of the rehabilitation and the esthetic outcome. Few clinical studies are available on the efficacy of these restorations, especially at longer follow-ups and with a large number of subjects. The objective of this study was therefore to retrospectively evaluate patients rehabilitated with screw-retained restorations using ASC. The time of delivery and their adherence to the maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Recent evidence suggests that angulated abutments might be associated with higher mechanical complications due to off‐axis loading and inferior preload on the abutment screw; this may result in premature screw loosening, followed by fracture and restoration failure (Hein et al, 2021; Hotinski & Dudley, 2019; Opler et al, 2020). However, clinical trials have reported high survival rates of 92%–96% for ASC reconstructions on titanium implants up to 3 years, with only a few technical complications (Di Fiore et al, 2023; Lv et al, 2021; Rella et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that angulated abutments might be associated with higher mechanical complications due to off‐axis loading and inferior preload on the abutment screw; this may result in premature screw loosening, followed by fracture and restoration failure (Hein et al, 2021; Hotinski & Dudley, 2019; Opler et al, 2020). However, clinical trials have reported high survival rates of 92%–96% for ASC reconstructions on titanium implants up to 3 years, with only a few technical complications (Di Fiore et al, 2023; Lv et al, 2021; Rella et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome poor esthetic results due to an access hole on the vestibular surface, the concept of angulated screw channels (ASCs) for titanium implants was introduced in 2015 (Garcia‐Gazaui et al, 2015; Pitman et al, 2022; Rella et al, 2021). Depending on the system, ASCs allow an axis correction of up to 25° and shift of the screw‐access hole to the more favorable palatal position (Edmondson et al, 2022; Rella et al, 2021). A recent cone‐beam computed tomography study compared the prevalence of screw‐retained reconstructions with straight versus angulated abutments in the anterior maxilla (Edmondson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Screw-retained implant-supported prostheses have the advantage of retrievability along with the elimination of residual cement that could lead to peri-implant diseases (Rella et al, 2021). However, placing an implant in an ideal position to locate the screw access channel in a nonvisible area may not be possible in some clinical conditions such as limited bone volume (Rasaie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new IAC system called TorcFit (Straumann AG), which offers an alternative to regular IAC of the same brand (CrossFit; Straumann AG) was introduced. Even though there are studies on angled screw channel system (Drew et al, 2020; Garcia‐Hammaker et al, 2021; Goldberg et al, 2019; Hu et al, 2019; Mulla et al, 2021; Rasaie et al, 2022; Rella et al, 2021; Swamidass et al, 2021), no study has ever investigated how this recently introduced IAC performs when restored with angled screw channel abutments. Therefore, the present study aimed to evaluate the effect of screw channel angle on the long‐term screw stability of this new IAC (TorcFit (TF)) and to compare it with that of the conventional IAC of the same brand (CrossFit (CF)), in which stable RTVs were demonstrated (Srimurugan‐Thayanithi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%